Preparation and flame retardancy of an Al2O3 infiltration layer on polycarbonate surface - Shibo Ren; Jianlin Xu; Lei Niu; Penghui Yang (Materials Research Express)
In this study, the surface flame retardancy of polycarbonate (PC) was improved and the impact of flame retardants on the substrate were minimized by pre-mixing Al _2 O _3 particles with dichloromethane, an infiltration promoter, to form a suspension, and then treating PC with the suspension to form an Al _2 O _3 infiltration layer. For this layer, its structure and composition were characterized, its flame retardancy was evaluated, and its flame retardancy mechanism was investigated. The characterization results confirmed that an Al _2 O _3 infiltration layer was successfully prepared on the PC surface under the aid of dichloromethane and that the involvement of dichloromethane induced certain microscopic pores and voids in the PC, with some dichloromethane remaining within the surface infiltration layer. The surface Al _2 O _3 infiltration layer mainly served as a condensed-phase flame retardant. The infiltration layer prepared using a suspension with a dichloromethane-to-Al _2 O _3 mass ratio of 24:1 not only exhibited a good overall performance but also achieved the best improvement in the PC flame retardancy, such as an increase in the vertical burning rating from HB to V-0, as well as the LOI increased from 24 to 31.3, and a 35% reduction in the peak heat release rate compared to those of pure PC.